Nickel(ii)-promoted specific hydrolysis of zinc finger proteins. Issue 8 (16th July 2018) - Belczyk-Ciesielska, Agnieszka; Csipak, Brigitta; Hajdu, Bálint; Sparavier, Aleksandra; Asaka, Masamitsu N.; Nagata, Kyosuke; Gyurcsik, Béla; Bal, Wojciech
Abstract : The (S/T)XH sequence in Cys2 His2 zinc fingers can be hydrolytically cleaved by Ni(ii ) ions. This reaction can be applied for purification, inhibition or activation of designed zinc finger fusion proteins. Abstract : In this work we demonstrate that the previously described reaction of sequence specific Ni(ii )-dependent hydrolytic peptide bond cleavage can be performed in complex metalloprotein molecules, such as the Cys2 His2 zinc finger proteins. The cleavage within a zinc finger unit possessing a (Ser/Thr)-X-His sequence is not hindered by the presence of the Zn(ii ) ions. It results in loss of the Zn(ii ) ion, oxidation of the SH groups and thus, in a collapse of the functional structure. We show that such natural Ni(ii )-cleavage sites in zinc finger domains can be edited out without compromising the DNA binding specificity. Inserting a Ni(ii )-susceptible sequence between the edited zinc finger and an affinity tag allows for removal of the latter sequence by Ni(ii ) ions after the protein purification. We have shown that this reaction can be executed even when a metal ion binding N-terminal His-tag is present. The cleavage product maintains the native zinc finger structure involving Zn(ii ) ions. Mass spectra revealed that a Ni(ii ) ion remains coordinated to the hydrolyzed protein product through the N-terminal (Ser/Thr)-X-His tripeptide segment. The fact that the Ni(ii )-dependent protein hydrolysis is influenced by the Ni(ii ) concentration, pH and temperature of the reaction provides a platform for novel regulated DNA effector design.